Quand le non-événement devient événement. Le discours sur la Deutsche Bank dans la presse française et polonaise - Rębkowska, Agata (Studia Romanica Posnaniensia, 2017)
In the last few years, the Deutsche Bank was facing difficulties which were regularly conceptualised by the international media. The aim of this paper is to study the meaning of the crisis and the role of the Deutsche Bank in the financial turmoil during the “discursive moment” initiated on February 8, 2016, as it was built by the French and Polish general press. On the basis of several articles published in six daily newspapers, we undertake a semantic analysis of nominal noun phrases referring to the current situation, and of the preferential discursive functioning of the chrematonyme Deutsche Bank.